2022
DOI: 10.1021/acs.orglett.2c00203
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Enabled, Ni-Catalyzed Cyanation of Aryl Halides

Abstract: A light-promoted Ni-catalyzed cyanation of aryl halides employing 1,4-dicyanobenzene as a cyanating agent is reported. A broad array of aryl bromides, chlorides, and druglike molecules could be converted into their corresponding nitriles (65 examples). Mechanistic studies suggest that upon irradiation, the oxidative addition product Ni(II)(dtbbpy)(p-C 6 H 4 CN)(CN) undergoes homolytic cleavage of the Ni−aryl bond to generate an aryl radical and a Ni(I)−CN species, the latter of which initiates subsequent cyana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Following the general procedure with 5-bromobenzo[d] [1,3]dioxole provided the desired product as a faint yellow crystal in 34% yield (123 mg, 0.84 mmol): 27 4-Phenoxybenzonitrile (10). Following the general procedure with 1-bromo-4-phenoxybenzne provided the desired product as a whiteyellow solid in 31% yield as determined by NMR: 1 32 Anthracene-9-carbonitrile (11). Following the general procedure with 9-bromoanthracene provided the desired product as a yellow solid in 40% yield as determined by NMR: 1 27 2-[1-Butyl-2-(propan-2-ylidene)hydrazineyl]-2-methylpropanenitrile (12).…”
Section: Synthesis Of Aibn-d 12mentioning
confidence: 99%
“…Following the general procedure with 5-bromobenzo[d] [1,3]dioxole provided the desired product as a faint yellow crystal in 34% yield (123 mg, 0.84 mmol): 27 4-Phenoxybenzonitrile (10). Following the general procedure with 1-bromo-4-phenoxybenzne provided the desired product as a whiteyellow solid in 31% yield as determined by NMR: 1 32 Anthracene-9-carbonitrile (11). Following the general procedure with 9-bromoanthracene provided the desired product as a yellow solid in 40% yield as determined by NMR: 1 27 2-[1-Butyl-2-(propan-2-ylidene)hydrazineyl]-2-methylpropanenitrile (12).…”
Section: Synthesis Of Aibn-d 12mentioning
confidence: 99%
“…As a result, it cannot participate in the final cyclization step. Nevertheless, fluorenes 7 ae , 7 ah and 7 aj [30] could be achieved in excellent yields of 78 %, 86 %, and 82 %, respectively, when strong acid TfOH (2.0 equiv) was used as the promoter for the final cyclization step of the reaction of 4 a with arylboronic acids flanked with electron‐withdrawing groups (e. g., fluoro, chloro, cyano) at the para ‐position.…”
Section: Resultsmentioning
confidence: 99%
“…A photochemical Ni-catalyzed cyanation of aryl bromides and chlorides was reported by Xue and co-workers. 18 They demonstrated that 1,4-dicyanobenzene (1,4-DCB) could be used as a cyano transfer agent with no other photosensitizer required in the transformation (Scheme 7). A screen of nickelbased precursors found that a mixture of NiI 2 (5 mol %), dtbbpy (5 mol %), (TMS) 3 SiH as a reducing agent, and DBU as a base gave the highest activity in this reaction upon purple light (390− 395 nm) irradiation.…”
Section: ■ Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%
“…A photochemical Ni-catalyzed cyanation of aryl bromides and chlorides was reported by Xue and co-workers . They demonstrated that 1,4-dicyanobenzene (1,4-DCB) could be used as a cyano transfer agent with no other photosensitizer required in the transformation (Scheme ).…”
Section: Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%